Exercise-based telerehabilitation for patients with multiple sclerosis using physical activity: a systematic review - Michaela Sladeckova; Jan Kocica; Eva Vlckova; Filip Dosbaba; Garyfallia Pepera; Jing Jing Su; Ladislav Batalik (Medical Journals Sweden, 2024)
Background: Telerehabilitation is a practical option for individuals with multiple sclerosis (MS) to engage in sustained physical activity without -visiting a rehabilitation facility. The aim of this systematic review was to evaluate the feasibility, effectiveness, safety, and adherence of exercise-based telerehabilitation as compared with usual care for MS patients. Methods: A comprehensive literature search adhering to PRISMA guidelines was conducted, focusing on studies published in English since 2000. The systematic review protocol was registered in PROSPERO. The selection process involved strict criteria, including studies focusing on people with MS, telerehabilitation centred on regular exercise, a control group receiving usual care, valid exercise testing, and adherence to randomized controlled trial principles. Methodological quality was assessed using the TESTEX tool, ensuring rigour in study design and reporting. Results: Among the 281 records screened, 10 studies met the criteria. Telerehabilitation interventions varied in format and outcomes were assessed using diverse exercise tests and questionnaires. Despite variations, the studies collectively demonstrated promising feasibility and safety, with minimal withdrawals and minor adverse events. Effectiveness varied, with 5 out of 10 studies showing significant improvements in the intervention group. Adherence rates ranged from 38% to 100%. Conclusion: In most of the assessed aspects, telerehabilitation is comparable to regular centre-based rehabilitation.